Intermediary levels of government for the development of productive agglomerations: viable implementations for emerging countries. (25th September 2019) - Filho, Nelson Casarotto; Ferasso, Marcos; Saldanha, Jorge Alberto Velloso
Although the cluster concepts are well-stressed in literature, and in several industries intensities, there are still some contributions that can be addressed to emerging countries. This article has as main objective to discuss the regional space for the development focusing the productive agglomerations and proposes a model of multilevel governance to assist the process of regional development which is important to generate income and increase the quality of life of the inhabitants of a given region. The space for regional development stems from the confrontation of two vectors: the first is the scale for development projects and the second is that of cooperation. A framework is built based on literature and a possible implementation in a Brazilian cluster is analysed.